2014
DOI: 10.3109/17538157.2014.924949
|View full text |Cite
|
Sign up to set email alerts
|

Identifying health facilities outside the enterprise: challenges and strategies for supporting health reform and meaningful use

Abstract: Objective: To support collation of data for disability determination, we sought to accurately identify facilities where care was delivered across multiple, independent hospitals and clinics.Methods: Data from various institutions' electronic health records were merged and delivered as continuity of care documents to the United States Social Security Administration (SSA).Results: Electronic records for nearly 8,000 disability claimants were exchanged with SSA. Due to the lack of standard nomenclature for identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In recent years, IHIE observed that multiple HIE partners, including other HIE networks in Indiana, members of the eHealth Exchange national HIE, and private enterprise health systems within its own network, began implementing CCD interfaces to send and receive information about individual encounters as well as a patient's past medical history (15,16). A total of 58 facilities within the IHIE network regularly send CCDs within the exchange.…”
Section: Study Contextmentioning
confidence: 99%
“…In recent years, IHIE observed that multiple HIE partners, including other HIE networks in Indiana, members of the eHealth Exchange national HIE, and private enterprise health systems within its own network, began implementing CCD interfaces to send and receive information about individual encounters as well as a patient's past medical history (15,16). A total of 58 facilities within the IHIE network regularly send CCDs within the exchange.…”
Section: Study Contextmentioning
confidence: 99%
“…Electronic data sharing across institutions is hampered by the heterogeneous names and formats used to store clinical data. 7,8 Only by adopting syntactic and semantic data standards can EHRs become interoperable and capable of integrating vast stores of variously formatted clinical data. Aiming to make clinical data available when and where it is needed, the certification criteria for EHRs under HITECH requires the use of common messaging and vocabulary standards.…”
mentioning
confidence: 99%